Parathyroid adenoma in a 33 years female, manifesting as non-traumatic multiple bone fractures - Sardhara, Mihir; Reddy , Nikhil (International Surgery Journal, 2023)
A 33 years old female patient presented to OPD with chief complaints of prolonged fatigue, abnormal gait and difficulty in walking since 7 years. On further evaluation MRI pelvis revealed bilateral non-traumatic pelvic bone fractures, with high Serum parathyroid hormone level (1050 pcg/ml) and hypercalcemia. CECT Neck showed a well-defined soft tissue density lesion involving the posterior-inferior aspect of the right lobe of thyroid gland. Surgical resection was performed and histopathology revealed parathyroid adenoma. Clinical manifestations and PTH and calcium levels gradually decreased to normal after surgery. Patient’s symptoms gradually decreased over a period of 2 month after treatment of the underlying cause. In a young female presenting with bony pains and non-traumatic fractures, a differential diagnosis of parathyroid adenoma must be kept in mind.